2015
DOI: 10.1063/1.4907269
|View full text |Cite
|
Sign up to set email alerts
|

Second derivatives for approximate spin projection methods

Abstract: The use of broken-symmetry electronic structure methods is required in order to obtain correct behavior of electronically strained open-shell systems, such as transition states, biradicals, and transition metals. This approach often has issues with spin contamination, which can lead to significant errors in predicted energies, geometries, and properties. Approximate projection schemes are able to correct for spin contamination and can often yield improved results. To fully make use of these methods and to carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…60 Our group has expanded the AP model to include analytical first and second derivatives. 75,76 In fact, several works have shown the effectiveness of this model and demonstrated the condition for which this model is suitable. 64,65,77,78 To carry out AP calculations, two converged determinants are required: (…”
Section: Approximate Projection Methodsmentioning
confidence: 96%
“…60 Our group has expanded the AP model to include analytical first and second derivatives. 75,76 In fact, several works have shown the effectiveness of this model and demonstrated the condition for which this model is suitable. 64,65,77,78 To carry out AP calculations, two converged determinants are required: (…”
Section: Approximate Projection Methodsmentioning
confidence: 96%
“…70 Preliminary calculations following protocols developed in one of our labs and considering approximate (spin) projection models to remedy impacted energies, forces, and force constants suggested that spin-contamination should not negatively impact the PIMOM based spectral simulations reported in this study. [71][72][73][74][75][76][77][78] Molecular geometries for ground and excited states were optimized using standard methods, 79 and the reported PES minima were verified using analytical second-derivative calculations. 80,81 The methylene blue ground state S 0 optimized structure is of C 2v symmetry for both B3LYP and CAM-B3LYP.…”
Section: Condon Vibronic Spectral Calculationsmentioning
confidence: 99%
“…28 Calculations using the AP model employed local implementations of analytic first-and second-derivative programs. 11,26,27 The examination of J-coupling calculations used the test set reported by Peralta and Rudra. 29,30 Calculations have been carried out using five different functionals: B3LYP, 31,32 LC-ωPBE, 33,34 CAM-B3LYP, 35 B3PW91 36 and ωB97XD.…”
Section: Computational Detailsmentioning
confidence: 99%
“…25 It seems reasonable to expect that projection may alter the PES and yield different minimum energy structures than these previous reports. To support such studies, our group has extended the use of AP by developing and implementing efficient first and second derivatives, 26,27 making geometry optimization and force constant evaluations on AP-corrected PESs practical.…”
Section: Introductionmentioning
confidence: 99%